PERAN GURU MATA PELAJARAN IPS DALAM MENINGKATKAN KESADARAN BELAJAR SISWA DI SD NEGERI 32 WOJA KABUPATEN DOMPU - Wahyuddin (STKIP Al-Amin Dompu, 2022)
The teaching and learning process is one way to run the education system in order to create shared expectations. Students' behavior, of course, always changes because due to the age of students who are still 9 years old, the space for joining in is always large. Qualitative descriptive research method. The results of the study, show the role of the teacher in teaching using existing standards, and the teacher the way of education by providing space for students to be able to understand the material that has been taught.